RESPONSE OF ADDITIONAL Moringa oleifera LEAF MEAL IN RATION CONTAINS RICE HULL SUPLEMENTED WITH STARPIG TO PRODUCTION AND EGG PHYSICAL QUALITY OF BALI DUCK - A. A. A. S., Trisnadewi; Partama, I. B. G.; Yadnya, T. G. B. (Majalah Ilmiah Peternakan; Vol 23 No 1 (2020): Vol. 23 No.1 (2020)DO - 10.24843/MIP.2020.v23.i01.p02, 2020)
The study aimed to determine the response of Moringa oleifera leaf meal in ration contains rice hull supplemented with Starpig to production and quality of bali duck eggs. The study used a completely randomized design with four treatments as of control ration (without rice hull, Moringa leaf meal, and starpig = A), ration containing 10% rice hull (B), ration containing 10% rice hull and Moringa leaf meal (C), ration contains 10% rice hull, Moringa leaf meal and Starpig (D). Each treatment with four replications and each replication contains three female bali ducks. The variables observed were production and quality of egg consisting of feed consumption, number of egg, hen day production, egg average weight, egg total weight, and feed conversion ratio (FCR), and egg quality consisting of water, protein, fat and total cholesterol. The results showed that the addional of Moringa oleifera leaf meal in rice hull ration (B) significantly decreased the number of eggs and daily egg production than the treatment A, but treatment C and D significantly increased the number of eggs, daily egg production, egg average weight, egg total weight compared with treatment A. Additional of treatment B could increase the consumption of ration but treatment C and D not affect ration consumption. Treatment D significantly decreased FCR compared with treatment A. It can be concluded that the additional of Moringa oleifera leaf meal in ration contains rice hull supplemented with Starpig could improve production performance and physical quality of bali duck eggs.